Optimization of Quality Improvement and Production Capacity at Prayogo's Chicken Slaughterhouse SME - Tonny Yuniarto; Paulus Wisnu Anggoro; Baju Bawono (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2022)
Moyudan Subdistrict is an area that has several small industries of chicken farming. Partner who was the participant of this community service program, Prayogo’s Chicken Slaughterhouse, an SME in Yogyakarta, had a major obstacles to increase the production capacity of good, neat, clean, and hygienic chicken meat and meeting halal standards. In addition, this business still did not have chicken cutting standards according to factory standards (SNI 01-6160-1999). The cutting process was still done manually and conventionally, with mediocre quality and quantity. Production capacity was low, and many production operators experienced high fatigue in the hands and shoulders or experienced musculoskeletal fatigue. The expected transfer of technology in this program is the design of modifications to poultry cutting machines that suit the needs of this partner and is associated with the selection of portable poultry machine designs and manufacturing technologies that can later improve the quality and capacity of chicken meat processing according to halal standards. The results of this community service activity are; (1) one unit of portable poultry machine given to partner; (2) an increase in production capacity of 429% in terms of cutting capacity per day with smooth, precise, and accurate cutting quality; (3) reduced fatigue experienced by the production operators after the machine in operation. The chicken cutting capacity of Prayogo's Chickens Slaughterhouse can be increased by 4.29 times from 75 chickens a day to a maximum of 321 chickens a day.